ANALISIS PENENTUAN ZONA RESAPAN AIR TANAH DI KECAMATAN RUMBIA DAN RUMBIA TENGAH KABUPATEN BOMBANA - Ludfi Ludfi; M. Tufaila Hemon; Hasbullah Syaf (Jurnal Perencanaan Wilayah, 2018)
This study aimed to analyze the Outspreading direction of waterabsorption areas and the extent ofoutspread of water absorption areas at the subdistrict of rumbia and Central Rumbia in Bombana regency.The study used a descriptive method, i.e a survey method. Data were analyzed using an overlay techniquewhich combined a namber of data and maps using the SIG (Sistem Informasi Geografis) or GeographicalInformation system. Some Parameters that ware used to determine water absorption areas were land use,precipitation, slope angle, and the texture of the land under investigation. Result of data analysis showedthat there were 2 criteria to determine the suitability of water absorption. The less suitable zones were in thenorthern, southern to western areas, totaling 6.249.03 Ha or 78.00 % of the total of areas being researched.The unsuitable zones of water absorption was in the eastern area of the research, which were mostly theareas where people reside, totaling 1,760.97 Ha or 21.98 % of the total of areas under investigation.Keywords : absorption zona, Underground water